Face mask usage during COVID-19 pandemic in rural population of Madhyapradesh: A knowledge, attitude and practice study. - Harshal Kawanpure; Mahendra Gandhe (Public Health Review: International Journal of Public Health Research, 2022)
Introduction: A face mask is a perfect tool to control the spread of COVID-19 infection. Theknowledge, attitudes and practices toward the use of face masks will be helpful to understandsociety's readiness to accept and follow preventive guidelines from the health authorities. Baselineinformation collected in this study can be used for the implementation of the COVID-19 controlprogramme. Hence, this study was conducted.Material and methods: This is a cross-sectionalstudy conducted in a rural area of Madhyapradesh. House to house survey was completed to collectthe information on knowledge, attitude and practice regarding face masks.Result: Out of 400participants, 318 (79.5%) participants know that COVID-19 can be transmitted by respiratorydroplet and 253(63.3%) participants know that COVID-19 can be sent by contact route. Total349(87.3%) participants responded that wearing a face mask can prevent COVID-19 transmission.Maximum participants know about cloth masks, i.e. 367(91.8%) and surgical masks, i.e.277(69.3%).Conclusions: Maximum participants learn various types of face masks, and they alsoknow that they can prevent COVID-19 disease. Maximum participants had a positive attitudetowards wearing a face mask at crowded places. One crucial finding came out that some participantshad shared their face masks with other people. Maximum participants had motivated their familymembers for wearing a face mask. IEC activities can be conducted by a health worker in a rural areaon proper use, proper disposal and storage of face masks